Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fimmu.2022.1064033
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory role of metalloproteases in cancers: Current progress and future trends

Abstract: Metalloproteinases (MPs) is a large family of proteinases with metal ions in their active centers. According to the different domains metalloproteinases can be divided into a variety of subtypes mainly including Matrix Metalloproteinases (MMPs), A Disintegrin and Metalloproteases (ADAMs) and ADAMs with Thrombospondin Motifs (ADAMTS). They have various functions such as protein hydrolysis, cell adhesion and remodeling of extracellular matrix. Metalloproteinases expressed in multiple types of cancers and partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 211 publications
0
7
0
Order By: Relevance
“…Mechanistically, micropeptides are able to contribute to the tumor phenotype by affecting the tumor microenvironment like blood vessels and extracellular matrix (ECM). 91 For example, lncRNA BVES-AS1 was demonstrated to encode a 50-aa-length micropeptide termed BVES-AS1-201-50aa.This micropeptide increases the expression of PCNA and MMP9 in the tumor microenvironment, thus promoting CRC cells viability, migration, and invasion. 92 However, whether one micropeptide acts via several mechanisms to affect the phenotypes of the same tumor or whether one micropeptide plays diverse roles in different tumors via more subtle and specific mechanisms should be explored further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, micropeptides are able to contribute to the tumor phenotype by affecting the tumor microenvironment like blood vessels and extracellular matrix (ECM). 91 For example, lncRNA BVES-AS1 was demonstrated to encode a 50-aa-length micropeptide termed BVES-AS1-201-50aa.This micropeptide increases the expression of PCNA and MMP9 in the tumor microenvironment, thus promoting CRC cells viability, migration, and invasion. 92 However, whether one micropeptide acts via several mechanisms to affect the phenotypes of the same tumor or whether one micropeptide plays diverse roles in different tumors via more subtle and specific mechanisms should be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they have impacts on tumor phenotype, including cell proliferation, metastasis, invasion, and angiogenesis. Mechanistically, micropeptides are able to contribute to the tumor phenotype by affecting the tumor microenvironment like blood vessels and extracellular matrix (ECM) 91 . For example, lncRNA BVES‐AS1 was demonstrated to encode a 50‐aa‐length micropeptide termed BVES‐AS1‐201‐50aa.This micropeptide increases the expression of PCNA and MMP9 in the tumor microenvironment, thus promoting CRC cells viability, migration, and invasion 92 .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…ADAMTSs was particularly typical in the study of osteoarthritis, as their disintegrin domain has intercellular adhesion function, allowing them to directly adhere to the extracellular matrix and participate in regulating intracellular and extracellular signaling pathways during tumor cell invasion and migration, degrading the extracellular matrix and basement membrane [31]. Although the mechanism of ADAMTS in carcinogenesis had not been fully elucidated, recent studies had shown that differential expression of ADAMTS-1, -8, -9, and − 18 family members was associated with the occurrence and development of various tumors, including cell proliferation, migration, invasion, apoptosis, and angiogenesis [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are produced by cancer cells, CAFs, ECs and various immune cells in the TME ( Wang et al, 2022 ). Two previous studies on microarrays found that MMPs were significantly upregulated in pCR patients, which indicated that MMPs are potential biomarkers of CRT sensitivity ( Wen et al, 2014 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…TME plays a key role in regulating the immune response to cancer ( De Visser & Joyce, 2023 ). Extensive remodeling of ECM often occurs during cancer progression, and ECM is degraded by the matrix metalloproteinase (MMP) family ( Wang et al, 2022 ). MMPs are produced by a variety of tissues and cells in the TME, including cancer cells, CAFs, ECs, vascular smooth muscle, macrophages, neutrophils, and lymphocytes.…”
Section: Introductionmentioning
confidence: 99%